The Influence of Socio-Economic Status on Career Planning in the Bonai Tribe in Ulak Patian Village - Faisal Asmen; Suwarjo Suwarjo; Yosua Drita Prasetya Adi (Universitas Ahmad Dahlan, 2020)
The purpose of this study was to determine the effect of socioeconomic status on career planning in the Bonai tribe community in the Village of Ulak Patian, Kecamatan Kep fulfillment. This study uses a quantitative approach. The study population was the entire Bonai tribe population in Ulak Patian village, and the sample taken was the population who were taking the junior high school to tertiary education, totaling 55 people. Simple regression analysis technique. The instruments used were a socioeconomic status questionnaire and a career planning questionnaire. The results showed that there was a positive and significant influence on the socioeconomic status of career planning in the Bonai. Bonai people are advised to improve their socioeconomic status to determine better career planning alternatives. This study provides recommendations for research on career planning development in the Bonai tribal community.